The cabe from Cotacachi: betwen game and comunity dynamics - Zapata Muñoz, Sofia; Soria Gaspar, Rodrigo Daniel (Tierra Infinita, 2022)
This article presents some results of the research performed between the years 2018-2019 in the region of Cotacachi, the main objective was the registration of the cultural expression of Cabe, or spinning top. As a research tool, the ethnographic research method was applied. Among the most important results, it is evident that this practice has developed its own characteristics in relation to other locations both in the dynamics of the game and in the elements used. In this last aspect, is characteristic the manufacture by the master carpenters of the spinning top or Cabe and the wooden disks or balls. On the other hand, although the practice of the spinning top is mostly mestizo, the indigenous presence in these spaces has been an important contribution of this sport to promote the inclusion. The spinning top game, as a distinctive cultural manifestation of Cotacachi, takes place throughout the year, with an emphasis in all souls’ day, discovering dynamics of healthy competition, both between the traditional neighborhoods of the city and in indigenous communities, fostering a sense of appropriation public space and local identity, as a fundamental part of the socio-cultural relations of Cotacachi.
Keywords: etnography; Cabe; cultural manifestation; intangible heritage